Isolation, Characterization And Antibiotic Sensitivity Of Clostridium Perfringens Isolated From Diarrheic Goats - Verma, Dipti; Verma, Yamini; Swamy, Madhu; Dubey , Amita (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The present study was conducted for isolation, characterization and antibiotic sensitivity of Clostridium perfringens organism from diarrheic goats. A total of 25 rectal swabs were collected from different goat farms of Jabalpur (M.P.). Out of 25 rectal samples 15 (60%) were found to be positive for Clostridium perfringens. From the positive samples, antimicrobial sensitivity test was performed by discs diffusion method. Most of the isolates of Clostridium perfringens were found sensitive to Penicillin, Ciprofloxacin and Levofloxacin and resistant to Gentamycin, Streptomycin and Chloramphenicol. All the isolates except one were resistant to Neomycin.